The Analysis of Pneumatic Wheel Rim Deformation While Hitting an Obstacle - Tarkowski, Sławomir; Nieoczym, Aleksander; Caban, Jacek; Jilek, Petr; Sejkorová, Marie (My University, 2022)
he article presents the results of simulations using the finite element method (FEM) aimed at examining the extent of damage to the wheel rim as a result of hitting an obstacle. The obtained results can be used as comparative data during the performance of expert opinions to give an answer as to how the damage occurred. The data obtained from the FEM simulation can also be used in the process of geometric optimization of the rim, which aims to obtain a rim resistant to this type of damage.
Analýza deformace ráfku vozidlového kola při přejezdu překážky
Keywords: impact; finite element method; optimization; road safety; náraz; metoda konečných prvků; optimalizace; bezpečnost silničního provozu